High-strength and high-plasticity Ti2AlNb-based alloy and preparation method thereof
By adding Mo, Zr and Si elements to the Ti2AlNb-based alloy, and using vacuum smelting, homogenization treatment, hot rolling and heat treatment processes, the brittleness and processing difficulties of Ti2AlNb-based alloy in high temperature environments are solved, and the preparation of high-strength and high-plastic Ti2AlNb-based alloy thin plates are realized.
Patent Information
- Application Number
- CN202510069844.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-03-28
AI Technical Summary
The existing Ti2AlNb-based alloy has problems of brittleness and processing difficulties in high temperature environments, which limits its application in high-temperature components of aerospace.
By adding Mo, Zr and Si elements to the Ti2AlNb-based alloy, and using vacuum smelting, homogenization treatment, hot rolling and heat treatment, a Ti2AlNb-based alloy thin plate with high strength and high plasticity was prepared.
The high strength and high plasticity of Ti2AlNb-based alloy were achieved, the room temperature yield strength reached 1273MPa, and the elongation of fracture was 11.8%, which significantly improved its mechanical properties.
Smart Images

Figure CN119710426A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of Ti2AlNb-based alloy preparation, in particular to a high-strength and high-plasticity Ti2AlNb-based alloy and a preparation method thereof. Background Art
[0002] The materials used in aerospace engines are required to have the characteristics of low density, high strength and toughness, and good stability in high temperature environments. Among the commonly used metal materials, titanium alloys have been widely studied because they have lower density, higher specific strength and better creep resistance than nickel-based high-temperature alloys. After decades of development, through the continuous improvement of alloy composition, preparation method, heat treatment process, organization control and other conditions, the stable use temperature of titanium alloys has been increased from 350℃ of the first generation of high-temperature titanium alloys represented by Ti-6Al-4V alloy to the current 600℃. However, when the use temperature of titanium alloys exceeds 600℃, a "thermal barrier" problem will occur. For example, the currently widely used high-temperature titanium alloys such as IMI834 and Ti-600 are restricted by factors such as surface oxidation and decreased long-term organizational stability, and their upper limit temperature is difficult to break through 600℃. When the temperature is higher than 600℃, high-temperature titanium alloys lose their competitive advantage over nickel-based high-temperature alloys in the high-temperature field. Therefore, it is urgent to develop a new material with the characteristics of low density and high-temperature thermal strength for use in high-temperature parts of aerospace.
[0003] Adding a large amount of Al elements to titanium alloys can form TiAl-based intermetallic compounds (such as γ-TiAl, α2-Ti3Al), thereby significantly improving the oxidation resistance and high-temperature strength of the alloy, but the poor plasticity and toughness of TiAl-based alloys limit their development. Adding a large amount of Nb elements to Ti3Al alloys will form Ti2AlNb alloys dominated by O phases. This alloy was first discovered by Banerjee et al. in 1988 when studying Ti3Al-based alloys. Compared with nickel-based high-temperature alloys and traditional high-temperature titanium alloys, Ti2AlNb alloys have higher fracture toughness, better oxidation resistance and crack propagation resistance, and have greater potential in the manufacture of high-temperature aerospace parts. Ti2AlNb alloy sheets are widely used in engineering, but the brittleness of O phase and processing difficulties have significantly restricted its application scope. It has not yet been fully commercialized. Researchers have tried various methods to manufacture Ti2AlNb alloy sheets in order to obtain sheets with excellent mechanical properties. Therefore, it is necessary to further optimize the composition and processing technology of Ti2AlNb alloys to promote their engineering applications. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a high-strength and high-plasticity Ti2AlNb-based alloy and a preparation method thereof, so as to improve the mechanical properties of the Ti2AlNb-based alloy sheet, so that the Ti2AlNb-based alloy has high strength while maintaining good plasticity.
[0005] The present invention is achieved through the following technical solutions: A high-strength and high-plasticity Ti2AlNb-based alloy comprises, by atomic percentage, 22-22.5% Al, 25-25.5% Nb, 1-1.25% Mo, 1-1.25% Zr, 0.25-0.3% Si, and the balance Ti and other inevitable impurities.
[0006] Preferably, the room temperature yield strength of the high-strength and high-plasticity Ti2AlNb-based alloy is 1273 MPa, and the elongation at break is 11.8%.
[0007] A method for preparing a high-strength and high-plasticity Ti2AlNb-based alloy comprises the following steps: Step 1, in terms of atomic percentage, 22-22.5% Al, 25-25.5% Nb, 1-1.25% Mo, 1-1.25% Zr, 0.25-0.3% Si and the balance Ti are mixed uniformly and then vacuum-melted to obtain an ingot; Step 2, homogenizing the ingot in the B2 single-phase region; Step 3, rolling the homogenized ingot in the two-phase region of B2 phase and O phase; Step 4: heat-treating the alloy obtained after rolling in the two-phase region to obtain a high-strength and high-plasticity Ti2AlNb-based alloy.
[0008] Preferably, the vacuum melting method is as follows: The induction current of the vacuum melting is 650-700A, the current frequency is 20-25KHz, and the alloy is kept for 3-4 minutes after being completely melted, and an ingot is obtained after cooling; then the ingot is melted and cooled multiple times to obtain an ingot.
[0009] Preferably, the ingot homogenization treatment method is as follows: The ingot is kept in the B2 single-phase region for 1 to 1.5 hours, and the holding temperature of the B2 single-phase region is 1100°C to 1200°C.
[0010] Preferably, the insulation temperature of the two-phase region of the B2 phase and the O phase is 940°C to 950°C.
[0011] Preferably, the rolling method is as follows: The ingot is kept at 940℃~950℃ for 25~35min. After the holding is completed, it is taken out and rolled several times. The total deformation is 85%~88%. The pressing amount of each pass is 4%-8% of the total thickness of the ingot. The holding temperature is 10~20℃ lower than the phase transition point of the two-phase region.
[0012] Preferably, the temperature of the two-phase region in step 4 is 940°C to 950°C.
[0013] Preferably, the heat treatment method is as follows: The ingot after rolling in step 4 is kept at 940°C-950°C for 1.5 minutes and then quenched to obtain a high-strength and high-plasticity Ti2AlNb-based alloy.
[0014] Preferably, the quenching is water quenching or oil quenching.
[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The present application provides a high-strength and high-plasticity Ti2AlNb-based alloy. Through a simple hot rolling process, the amount of pressure per pass is changed in the B2+O dual-phase region to prepare a Ti2AlNb alloy sheet with excellent mechanical properties, with a room temperature yield strength of 1273MPa and a fracture elongation of 11.8%. At present, the room temperature mechanical properties of Ti2AlNb alloys are mostly concentrated in the range of yield strength of 900~1100MPa and fracture elongation of 3%~10%. The Ti2AlNb-based alloy sheet in the present invention has obvious advantages over other Ti2AlNb alloys. The excellent mechanical properties of the alloy sheet are due to the synergistic effect between the B2 and O phases during the hot rolling process. The average grain size of the O phase is less than 1μm through hot rolling, and the O phase is mostly equiaxed or nearly equiaxed. The refinement of the precipitated phase has a significant effect on the improvement of the mechanical properties of the alloy. The addition of Mo element to Ti2AlNb-based alloy plays a role of multi-component composite solid solution strengthening, refines the O phase structure, adjusts the microstructure, and improves the strength of the alloy; Zr element mainly affects the high-temperature mechanical properties of the alloy. An appropriate amount of Zr element will improve the oxidation resistance and creep strength of the alloy while maintaining the room temperature strength and ductility unchanged. Si element often exists in the alloy in the form of solid solution and silicide, and is located at the grain boundary to improve the mechanical properties of the material by pinning dislocations. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0017] Figure 1 This is a SEM microstructure picture of the Ti2AlNb-based alloy of the present invention after high-temperature homogenization is completed; Figure 2 The room temperature tensile curves of the Ti2AlNb-based alloy of the present invention after undergoing different hot rolling mechanisms; Figure 3 A comparison of mechanical properties between the Ti2AlNb-based alloy of the present invention and other Ti2AlNb alloys; Among them, Figure a is a comparison of yield strength and elongation at break, and Figure b is a comparison of (tensile strength × elongation at break) and yield strength; Figure 4 This is a SEM microstructure picture of the Ti2AlNb-based alloy after hot rolling of the present invention; Among them, Figure a is the SEM image of each pass with a 4% (0.5 mm) press, and Figure b is the SEM image of each pass with a 8% (1 mm) press; Figure 5 This is the EBSD image of the Ti2AlNb-based alloy after hot rolling of the present invention; Among them, Figure a is a picture of the precipitated phase distribution with a pressing of 4% (0.5mm) per pass, Figure b is a picture of the B2 phase IPF with a pressing of 4% (0.5mm) per pass, Figure c is a picture of the precipitated phase distribution with a pressing of 8% (1mm) per pass, and Figure d is a picture of the B2 phase IPF with a pressing of 8% (1mm) per pass. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.
[0019] Therefore, the following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for which protection is sought, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0020] Ti2AlNb-based alloy is a complex multiphase alloy system. Different components will have a great impact on the transformation temperature, morphology, distribution, quantity and alloy properties of the precipitated phase. This application takes reducing alloy cost, reducing alloy density, and improving the comprehensive mechanical properties of the alloy as the starting point, and designs and optimizes the alloy composition to prepare a Ti2AlNb-based alloy that meets the requirements.
[0021] A high-strength and high-plasticity Ti2AlNb-based alloy comprises, by atomic percentage, 22-22.5% Al, 25-25.5% Nb, 1-1.25% Mo, 1-1.25% Zr, 0.25-0.3% Si, and the balance Ti and other inevitable impurities.
[0022] The above-mentioned Ti, Al, Nb, Mo, Zr and Si elements are all high-purity titanium, high-purity aluminum, high-purity molybdenum, high-purity zirconium, high-purity zirconium and high-purity silicon.
[0023] Based on the above high-strength and high-plasticity Ti2AlNb-based alloy, correspondingly, the present application also provides a method for preparing the high-strength and high-plasticity Ti2AlNb-based alloy, comprising the following steps: Step 1: Prepare, by atomic percentage, 22-22.5% Al, 25-25.5% Nb, 1-1.25% Mo, 1-1.25% Zr, 0.25-0.3% Si and the balance Ti.
[0024] Step 2: uniformly mix the above raw materials and put them in bulk into a non-consumable vacuum arc melting furnace for multiple vacuum melting to obtain an ingot. The melting method is as follows: Mix all the raw materials evenly and put them in bulk into a non-consumable vacuum arc melting furnace. Turn on the high-purity argon gas bottle and wash the gas before vacuuming. Fill the high-purity argon gas after each pumping to 3Pa. Repeat this operation three times. After the washing is completed, vacuum the arc melting furnace until the pressure in the furnace is less than 3×10 -3 After the vacuum is evacuated, high-purity argon gas is injected to maintain the argon atmosphere in the furnace.
[0025] Then, the alloy raw materials are melted, the induction current is 650~700A, the current frequency is 20~25KHz, and the alloy is completely melted and maintained for 3~4 minutes, and then the ingot is obtained after cooling. Then the ingot is turned over and continued to be melted. After melting ≥2 times, the electromagnetic stirring is turned on and the melting is continued according to the above parameters for ≥7 times to ensure the uniformity of the composition and avoid segregation of the alloy ingot. After the melting is completed, the ingot is cooled in a water-cooled copper crucible to obtain an ingot.
[0026] Step 3: homogenize the ingot in the B2 single-phase region.
[0027] Specifically, the alloy ingot is subjected to high temperature homogenization treatment, kept at 1100° C. to 1200° C. (B2 single-phase region) for 1 to 1.5 hours, and then water-cooled.
[0028] The homogenization temperature should be 50~150℃ higher than the phase transformation point of the B2 single-phase region (1050℃) and kept warm for 1~1.5 hours to ensure that the alloy is composed of all B2 grains.
[0029] Step 4: rolling the homogenized ingot in the two-phase region, and the rolling method is as follows: The ingot is kept at 940℃~950℃ (B2+O two-phase region) for 25~35min. After the insulation is completed, it is taken out and rolled several times. The pressing amount of each pass is 4%-8% of the total thickness of the ingot. After each rolling, it is returned to the furnace for insulation for 1.5min. The total deformation is about 85%~88%.
[0030] The holding temperature should be 10~20℃ lower than the phase transition point (960℃) of the B2+O two-phase region. The holding time should be 25~35min to ensure that a sufficient amount of O phase is precipitated. The total variable should be controlled at about 85%~88% to ensure that the alloy sheet has sufficient tensile strength.
[0031] Step 5: The ingot rolled in step 4 is kept at 940° C. to 950° C. for 1.5 min and then quenched to obtain a high-strength and high-plasticity Ti2AlNb-based alloy.
[0032] The alloy plate is composed of an equiaxed or nearly equiaxed O phase and a B2 matrix; the average grain size of the O phase is less than 1 μm.
[0033] The present application prepares a Ti2AlNb alloy sheet with both high strength and high plasticity through a simple hot rolling process, which does not require subsequent heat treatment, greatly shortens the production cycle, and significantly reduces the production cost. After being kept in the B2+O dual phase region for 25 to 35 minutes, the alloy sheet is pressed down by about 4% of the initial thickness each time, which makes the alloy sheet have excellent mechanical properties, and its room temperature yield strength reaches 1273MPa, and the elongation at break is 11.8%. At present, the yield strength of Ti2AlNb-based alloys is mostly concentrated in 900~1100MPa, and the elongation at break is mostly concentrated in 3~10%. The performance of the alloy sheet in the present invention is significantly better than other Ti2AlNb-based alloys, and has a greater competitive advantage. The microstructure after hot rolling is composed of equiaxed or nearly equiaxed O phase and B2 matrix. Hot rolling significantly refines the O phase grain size, with an average size of <1μm, and the refinement of the precipitate phase has a positive effect on the improvement of strength; the O phase is distributed in an equiaxed or nearly equiaxed shape, which has a positive effect on plasticity.
[0034] Example 1 A method for preparing a high-strength and high-plasticity Ti2AlNb-based alloy comprises the following steps: Step 1. High-purity titanium, high-purity aluminum, high-purity niobium, high-purity molybdenum, high-purity zirconium and high-purity silicon with a purity of 99.9% are uniformly mixed according to the above atomic percentages and placed in bulk into a non-consumable vacuum arc melting furnace, wherein each element, by atomic percentage, includes 22% Al, 25% Nb, 1% Mo, 1% Zr, 0.25% Si, and the remainder is Ti and other inevitable impurities.
[0035] Step 2: Mix the alloy raw materials evenly and put them into the furnace, then evacuate the arc melting furnace, turn on the high-purity argon gas bottle, and purge before evacuating. Each time the pressure is evacuated to 3Pa, fill with high-purity argon gas, and repeat this operation three times. After the purge is completed, evacuate the arc melting furnace until the pressure in the furnace is less than 3×10 -3 After the vacuum is evacuated, high-purity argon gas is injected to maintain the argon atmosphere in the furnace.
[0036] Step 3: Melt the alloy raw materials with an induction current of 650A and a current frequency of 20KHz. After the alloy is completely melted, keep the current for 3 minutes and obtain an ingot after cooling. Then turn the ingot over and continue to melt. After melting for ≥2 times, turn on the electromagnetic stirring and continue to melt for ≥5 times according to the above parameters to ensure the uniformity of the composition. After melting, cool the ingot in a water-cooled copper crucible to obtain an ingot.
[0037] Step 4: Perform high temperature homogenization treatment on the alloy ingot, keep it at 1100℃ (B2 single phase region) for 1 hour, and then cool it with water. Figure 1 As shown, heat preservation in the B2 single-phase region makes the alloy composed of uniform B2 phase grains with larger size.
[0038] Step 5: Cut the homogenized ingot into blocks with a size of 13 mm × 15 mm × 20 mm using a wire cutter. Keep the ingot at 940°C (B2+O two-phase region) for 30 minutes, and take it out for rolling after the heat preservation is completed.
[0039] The initial rolling thickness is 13mm, and the pressing amount of each sample is about 4% (0.5mm) of the initial thickness, which is recorded as sample A. After rolling, the sample is returned to the furnace for 1.5 minutes of heat preservation and then continued to roll. The thickness after rolling is about 1.5~2mm, and the total deformation is about 85%~88%. When approaching the end, the single pressing amount can be appropriately reduced to prevent the alloy from cracking due to the large single deformation in the late stage of hot rolling.
[0040] Step 6: The alloy plate is kept at 940° C. for 1.5 min and then quenched to obtain a high-strength and high-plasticity Ti2AlNb-based alloy sheet.
[0041] Example 2 A method for preparing a high-strength and high-plasticity Ti2AlNb-based alloy comprises the following steps: Step 1. High-purity titanium, high-purity aluminum, high-purity niobium, high-purity molybdenum, high-purity zirconium and high-purity silicon with a purity of 99.9% are uniformly mixed according to the above atomic percentages and placed in bulk into a non-consumable vacuum arc melting furnace, wherein each element, by atomic percentage, includes 22.5% Al, 25.5% Nb, 1.25% Mo, 1.25% Zr, 0.3% Si, and the remainder is Ti and other inevitable impurities.
[0042] Step 2: Mix the alloy raw materials evenly and put them into the furnace, then evacuate the arc melting furnace, turn on the high-purity argon gas bottle, and purge before evacuating. Each time the pressure is evacuated to 3Pa, fill with high-purity argon gas, and repeat this operation three times. After the purge is completed, evacuate the arc melting furnace until the pressure in the furnace is less than 3×10 -3 After the vacuum is evacuated, high-purity argon gas is injected to maintain the argon atmosphere in the furnace.
[0043] Step 3: Melt the alloy raw materials with an induction current of 700A and a current frequency of 25KHz. After the alloy is completely melted, keep it for 4 minutes and cool it to obtain an ingot. Then turn the ingot over and continue to melt it. After melting for ≥2 times, turn on the electromagnetic stirring and continue to melt for ≥5 times according to the above parameters to ensure the uniformity of the composition. After melting, cool it in a water-cooled copper crucible to obtain an ingot.
[0044] Step 4: Perform high-temperature homogenization treatment on the alloy ingot, keep it at 1200°C (B2 single-phase region) for 1.5 hours, and water-cool it after the insulation is completed.
[0045] Step 5. Use wire cutting to cut the homogenized ingot into blocks of 13mm×15mm×20mm in size, keep them at 950℃ (B2+O two-phase region) for 35min, and take them out for rolling after the insulation is completed. The initial rolling thickness is 13mm, and the amount of pressure of each pass of the sample is about 8% (1mm) of the initial thickness, recorded as sample B. After rolling, return to the furnace and keep warm for 1.5min before continuing to roll. The finished thickness is about 1.5~2mm, and the total deformation is about 85%~88%. When approaching the final thickness, the single pressure can be appropriately reduced to prevent cracking of the alloy due to large single deformation in the later stage of hot rolling. The room temperature tensile curves of sample A and sample B are shown in the figure. Figure 2 As shown; compared with the mechanical properties of other Ti2AlNb alloys Figure 3 As shown, Figure (a) is the yield strength σ y vs. Elongation at break ε f Comparison pictures, Figure (b) shows the tensile strength σ UTS ×Elongation at breakε f vs. Yield strength σ y Compare pictures.
[0046] Step 6: After the last rolling pass, the alloy plate is kept at 950°C for 1.5 minutes and then quenched to obtain a high-strength and high-plasticity Ti2AlNb-based alloy sheet.
[0047] Example 3 The preparation method of this embodiment 3 is basically the same as the method of embodiments 1 and 2, except that the percentage of each raw material and the process parameters are as follows: A method for preparing a high-strength and high-plasticity Ti2AlNb-based alloy comprises the following steps: Step 1: The elements, by atomic percentage, include 22.3% Al, 25.4% Nb, 1.18% Mo, 1.2% Zr, 0.28% Si, and the balance is Ti and other inevitable impurities.
[0048] Step 2: Mix the alloy raw materials evenly and put them into the furnace, then evacuate the arc melting furnace, turn on the high-purity argon gas bottle, and purge before evacuating. Each time the pressure is evacuated to 3Pa, fill with high-purity argon gas, and repeat this operation three times. After the purge is completed, evacuate the arc melting furnace until the pressure in the furnace is less than 3×10 -3 After the vacuum is evacuated, high-purity argon gas is injected to maintain the argon atmosphere in the furnace.
[0049] Step 3: Melt the alloy raw materials with an induction current of 680A and a current frequency of 22KHz. After the alloy is completely melted, keep the current for 3.5 minutes and obtain an ingot after cooling. Then turn the ingot over and continue to melt. After melting for ≥2 times, turn on the electromagnetic stirring and continue to melt for ≥5 times according to the above parameters to ensure the uniformity of the composition. After melting, cool the ingot in a water-cooled copper crucible to obtain an ingot.
[0050] Step 4: Perform high-temperature homogenization treatment on the alloy ingot, keep it at 1150°C (B2 single-phase region) for 1.2 hours, and water-cool it after the insulation is completed.
[0051] Step 5: Cut the homogenized ingot into blocks of 13mm×15mm×20mm using a wire cutter, keep it at 945℃ (B2+O two-phase region) for 30min, and take it out for rolling after the insulation is completed. The initial rolling thickness is 13mm, and the amount of pressure per pass of the sample is about 8% (1mm) of the initial thickness, recorded as sample C. After rolling, return to the furnace and keep it for 1.5min to continue rolling. The thickness after rolling is about 1.5~2mm, and the total deformation is about 85%~88%. When it is close to 1.5mm, the single pressure can be appropriately reduced to prevent the alloy from cracking due to the large single deformation in the later stage of hot rolling.
[0052] Step 6: After the last rolling pass, the alloy plate is kept at 945°C for 1.5 minutes and then quenched to obtain a high-strength and high-plasticity Ti2AlNb-based alloy sheet.
[0053] The preparation method of the present application keeps the homogenized alloy at 940℃~950℃ (B2+O dual-phase region) for 25~35 minutes and then controls the pressing amount per pass to prepare a Ti2AlNb alloy sheet with excellent mechanical properties. When the pressing amount per pass is 4% of the initial thickness, the yield strength of the sheet obtained is 1273MPa, and the elongation at fracture is 11.8%; when the pressing amount per pass is 8% of the initial thickness, the yield strength of the sheet obtained is 1253MPa, and the elongation at fracture is 7.8%. After hot rolling, the O phase is mostly distributed in an equiaxed or nearly equiaxed shape, which has a positive effect on plasticity. Increasing the pressing amount per pass makes the O phase tend to be distributed in a strip-like shape. The micromorphology of the alloy after hot rolling is as follows. Figure 4 As shown, Figure (a) is the SEM image of the sample with a pressing amount of 4% of the initial thickness per pass, and Figure (b) is the SEM image of the sample with a pressing amount of 8% of the initial thickness per pass. Hot rolling will refine the alloy grains. When the pressing amount per pass is 4% of the initial thickness, the average grain size of the O phase is less than 1μm. Increasing the pressing amount increases the volume fraction of the O phase from 11.3% to 24.7%. Dynamic recrystallization of the B2 phase occurs during hot rolling, and there are B2 grains with significantly different orientations from the surrounding grains. The specific EBSD characterization is as follows Figure 5 As shown, Figure (a) and (c) are the distribution pictures of the precipitate phase content after hot rolling, and Figure (b) and (d) are the IPF pictures of the B2 phase.
[0054] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A high-strength and high-plasticity Ti2AlNb-based alloy, characterized in that: Calculated by atomic percentage, it includes 22~22.5% Al, 25~25.5% Nb, 1~1.25% Mo, 1~1.25% Zr, 0.25~0.3% Si, and the balance is Ti and other inevitable impurities.
2. A high-strength and high-plasticity Ti2AlNb-based alloy according to claim 1, characterized in that: The room temperature yield strength of this high-strength and high-plasticity Ti2AlNb-based alloy is 1273MPa and the elongation at break is 11.8%.
3. A method for preparing a high-strength and high-plasticity Ti2AlNb-based alloy, characterized in that: The following steps are involved: Step 1, in terms of atomic percentage, 22-22.5% Al, 25-25.5% Nb, 1-1.25% Mo, 1-1.25% Zr, 0.25-0.3% Si and the balance Ti are mixed uniformly and then vacuum-melted to obtain an ingot; Step 2, homogenizing the ingot in the B2 single-phase region; Step 3, rolling the homogenized ingot in the two-phase region of B2 phase and O phase; Step 4: heat-treating the alloy obtained after rolling in the two-phase region to obtain a high-strength and high-plasticity Ti2AlNb-based alloy.
4. The method for preparing a high-strength and high-plasticity Ti2AlNb-based alloy according to claim 1, characterized in that: The method of the vacuum melting is as follows: The induction current of the vacuum melting is 650-700A, the current frequency is 20-25KHz, and the alloy is kept for 3-4 minutes after being completely melted, and an ingot is obtained after cooling; then the ingot is melted and cooled multiple times to obtain an ingot.
5. The method for preparing a high-strength and high-plasticity Ti2AlNb-based alloy according to claim 1, characterized in that: The homogenization treatment method of the ingot is as follows: The ingot is kept in the B2 single-phase region for 1 to 1.5 hours, and the holding temperature of the B2 single-phase region is 1100°C to 1200°C.
6. The method for preparing a high-strength and high-plasticity Ti2AlNb-based alloy according to claim 1, characterized in that: The insulation temperature of the two-phase region of the B2 phase and the O phase is 940°C to 950°C.
7. The method for preparing a high-strength and high-plasticity Ti2AlNb-based alloy according to claim 6, characterized in that: The rolling method is as follows: The ingot is kept at 940℃~950℃ for 25~35min. After the holding is completed, it is taken out and rolled several times. The total deformation is 85%~88%. The pressing amount of each pass is 4%-8% of the total thickness of the ingot. The holding temperature is 10~20℃ lower than the phase transition point of the two-phase region.
8. The method for preparing a high-strength and high-plasticity Ti2AlNb-based alloy according to claim 1, characterized in that: The temperature of the two-phase region in step 4 is 940°C to 950°C.
9. The method for preparing a high-strength and high-plasticity Ti2AlNb-based alloy according to claim 8, characterized in that: The heat treatment method is as follows: The ingot after rolling in step 4 is kept at 940°C-950°C for 1.5 minutes and then quenched to obtain a high-strength and high-plasticity Ti2AlNb-based alloy.
10. The method for preparing a high-strength and high-plasticity Ti2AlNb-based alloy according to claim 9, characterized in that: The quenching is water quenching or oil quenching.
Citation Information
Cited By
Preparation method of phase composition controllable Ti2AlNb thin strip based on thin strip cast rolling
CN121911839A
A method for preparing Ti2AlNb thin strips with controllable phase composition based on thin strip casting and rolling
CN121911839B